Historical development of individual nouns in English and Uzbek (comparative analysis) - Babajanova, Iqbol (The Lingua Spectrum, 2025)
In recent years, a lot of attention has been paid to the system of teaching foreign languages in our country. From this point of view, the teaching of a foreign language, especially English, is taking a new level. This requires comparative studies today. It follows that this article provides analyzes based on a comparative approach to the historical development of individual horses in English and Uzbek. Special, controversial information about the importance of individual horses in English linguistics and the current Uzbek literary language and its development has been scientifically-theoretically analyzed.